AR i VR w edukacji i terapii dziecka z niepełnosprawnością intelektualną - Piotrowska-Madej, Klaudia; Lewandowski, Paweł; Madej , Łukasz (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article presents educational values and dangers related to the use of augmented and virtual reality technology. Selected applications available on the Polish market and solutions dedicated to children with disabilities developed by the authors were presented, too.